Impact of infrastructure on trade and foreign direct investment in Malaysia - Ahmad, Nor Asma (2012)
This study examines the impact of infrastructure on trade and FDI in Malaysia from 1980 to 2008. The first analysis aims to test the theoretical assumption whereby the improvements in infrastructure will reduce the trade costs and will be able to enhance trading opportunities by including selected infrastructure indicators in the augmented gravity equation. A panel data is employed to capture the impact of different types of infrastructure on trade between Malaysian and its 36 trading partner whereas for the second analysis, time series of Malaysian data is estimate to capture the impact of infrastructure on FDI by using ARDL method. The results reveal that the physical, non-physical and soft infrastructure has positive impact in boosting the level of Malaysian exports. Empirical results also support that the improvement in infrastructure will affect FDI into Malaysia positively.